OS 06-09 THE SYNERGISTIC ASSOCIATION BETWEEN VITAMIN D AND VITAMIN K WITH INCIDENT HYPERTENSION. (September 2016) - Van Ballegooijen, Adriana; Van Schoor, Natasja; Brouwer, Ingeborg; Visser, Marjolein; Beulens, Joline
Abstract : Objective: Vitamin D plays an important role in calcium homeostasis. The role of vitamin D in bone and cardiovascular health has mainly been studied in isolation and the synergistic effect of vitamin D and vitamin K is largely unknown. We assessed whether serum 25-hydroxyvitamin D [25(OH)D] levels and dephosphorylated, uncarboxylated matrix Gla protein (dp-unMGP) levels –an established marker of vitamin K status– are associated with incident hypertension among older adults in the Netherlands. Design and Method: We used data from the Longitudinal Aging Study Amsterdam (LASA), a population-based, prospective cohort with baseline measurements obtained between 2002 and 2003 and 3 follow-up exams. We studied 257 men and women, aged 55 to 65 years free of prevalent cardiovascular disease, hypertension and use of anti-hypertensive medication with follow-up data. We measured serum 25(OH)D and dp-ucMGP from previously frozen baseline samples. We used Cox-regression analyses to estimate hazard ratios and 95% confidence intervals for 25(OH)D and dp-ucMGP categories with incident hypertension through 2012 (blood pressure ≥140/90 mmHg or initiation of blood pressure-lowering drugs). Results: During a median follow-up of 6.1 years, 52% of the cohort (n = 133) developed hypertension. Mean ± SD serum concentration of 25(OH)D was 58.9 ± 22.3 nmol/L and median dp-ucMGP was 310 (IQR: 209–425) nmol/L. Compared with the category of 25(OH)D ≥50nmol/L and dp-ucMGP < 310 nmol/L, the category 25(OH)D < 50 nmol/L and dp-ucMGP ≥310 was associated with a greater hazard ratio for incident hypertension: 1.72 (1.06, 2.81) adjusting for age, sex, body mass index, and type 2 diabetes. This hazard ratio was larger than for serum 25(OH)D < 50 nmol/L or dp-ucMGP≥310 nmol/L: HR 1.08 (0.67, 1.72) and 1.43 (0.85, 2.41), respectively. Conclusions: Serum 25(OH)D and dp-ucMGP are synergistically associated with a greater risk of developing hypertension. Randomized controlled trials should investigate whether supplementation of both vitamin D and vitamin K can lower blood pressure and hypertension risk.